Impact of dynamic thermal conductivity change of EPS insulation on temperature variation through a wall assembly. (June 2021) - Khoukhi, Maatouk; Abdelbaqi, Shaimaa; Hassan, Ahmed; Darsaleh, Abeer
Abstract: This paper evaluates the effect of dynamic thermal conductivity (λ) change of expanded polystyrene insulation (EPS) on temperature change through a conventional wall assembly at varying positions of the insulation within the assembly in question. According to the findings, in the case of the application of the variable λ-value of the insulation, compared to that obtained when the constant λ-value for polystyrene (EPS) insulation is adopted in the same conditions, the temperature profile through the wall assembly during the daytime is greater. In the event of applying the constant and variable λ-values, the temperature shift on the inside is seen to decline as the location of the insulation material is positioned towards the surface of the inner wall. The highest level of time lag between position 1 to 2 is over 1.3 h and around 3.47 h between position 1 and 3, and as the density level of the insulation materials rises, it leads to better transient thermal performance due to a lower temperature rise on the inside wall surface. These results suggest that considering betterment in the insulation's thermal conductivity would provide the most performant wall configuration by placing the material in the middle of the wall assembly, taking into account the change in the thermal conductivity of the insulation.